Modulation of the Interleukin-6 Receptor Subunit Glycoprotein 130 Complex and Its Signaling by LMO4 Interaction - Novotny-Diermayr, Veronica; Lin, Baohong; Gu, Lei; Cao, Xinmin (The Journal of biological chemistry, 2005)
The interleukin (IL)-6-type cytokines play major roles in a variety of biological processes by signaling through a common receptor subunit, glycoprotein (gp) 130. We performed yeast two-hybrid screening to identify new binding partners of the activated gp130 and the associated Janus kinases. LMO4, a LIM domain-containing protein that belongs to a family of oncogenes, was identified in this assay. Further studies show that LMO4 associates with gp130 and Janus kinase1 in several mammalian cell types. It also interacts with protein-tyrosine phosphatase 2 (SHP2) and suppressor of cytokine signaling 3 (SOCS3). The binding domains involved in these interactions were mapped, and the interactions were shown to be in a direct manner by in vitro binding assays. It is likely that LMO4 exists in the gp130 complex. The cellular localization of LMO4 was detected primarily in the nucleus with a substantial amount also detected in the cytoplasm in several cell types. The effect of LMO4 in IL-6 signaling was subsequently examined. Overexpression of LMO4 enhanced the transcriptional activity and target gene expression of Stat 3 (signal transducers and activators of transcription 3). Consistent with this, silencing LMO4 expression in stable cell lines expressing the small interfering RNA of LMO4 decreased Stat3 activity. Furthermore, the half-life of gp130 was shortened, and the production of acute phase proteins induced by IL-6 was reduced. Together, our data reveal a positive regulatory role of LMO4 in IL-6 signaling, possibly by acting as a scaffold for stabilization of the gp130 complex. These studies may open up a link between the oncogenic effect of LMO proteins and their regulatory role in cytokine signaling in general.